Estimation of corrosion vulnerability using GIS - Anastasiou, Constantina (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The aim of this master thesis is to produce corrosion risk maps using GIS tools. Firstly the corrosion theory, the theory of the corrosion due to chlorides, the theory of the lab tests and the theory of GIS tools is presented. Then, the factors which are contributed to the initiation of the corrosion in the reinforced concrete structures are analyzed. Next, will be further analysis of the most important factors which contribute to the initiation of corrosion, to create a model showing the risks of a structure or an area with respect of corrosion. Subsequently, the corrosion risk model will be inserted in a GIS program in order to create the corrosion risk maps. The examine area is Limassol city. Although, this model could be applied in every area the engineer wants, after some changes that should be done in the model. By doing this, the engineer will know the corrosion risk of the structure.
Keywords: Corrosion; Chlorides; Geographical Information System (GIS); Mathematical model; Limassol risk map; Διάβρωση; Χλωριόντα; Γεωγραφικά Συστήματα Πληροφοριών (ΓΣΠ); Μαθηματικό μοντέλο; Χάρτης επικινδυνότητας Λεμεσού